Logística en los procesos de almacenamiento y despacho de la distribuidora Álvarez- Babahoyo. - Cedeño Álvarez, Clemencia Stefania (2022)
The purpose of this research work is to study the logistics in the storage and dispatch processes of the Distribuidora Álvarez in the city of Babahoyo, the objective is to analyze the causes that have generated a defective logistics process, disconnected both to the company and to the client, the methodology of the investigation that was improved was descriptive and analytical, in addition the information collection technique was used, which was accompanied by an instrument such as the interview, through this the real problems that are being raised were verified at the Distribuidora Álvarez. The need to investigate the case study is due to all the drawbacks that can be evidenced, such as; the lack of staff training, the delay in delivering the orders requested by the clients, the poor planning and coordination of the collaborators, the inadequate management of inventory control, among other factors that cause the business not to meet its goals and projected objectives having as a consequence the loss of productivity of the company due to the lack of knowledge of the workers according to their respective jobs, loss of clients, decrease in sales, low profitability.